2006
DOI: 10.1136/jcp.2005.032037
|View full text |Cite
|
Sign up to set email alerts
|

Hypoplasia and neuronal immaturity of the hypoglossal nucleus in sudden infant death

Abstract: Objective: To report the case of five month old female baby with a history of episodes of gastrooesophageal reflux and pneumonia. Her sudden death offered a unique insight into the possible role of delayed neuronal maturation and hypoplasia of the hypoglossal nucleus in representing a likely morphological substrate of sudden death. Methods: Morphometric analysis was carried out with an Image-Pro Plus Image analyser (Media Cybernetics) on both sides of the brain stem. Results: Hypoplasia and neuronal immaturity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…However, alterations in the breathing-related modulation of hypoglossal motoneurons have been considered to be involved in sleep obstructive apnea [28][29][30]. Previous studies have shown that during specific experimental conditions, such as hypercapnia-hypoxia or lung inflation, the XII rhythmic activity might not be perfectly coupled to other respiratory motor outputs such as phrenic motoneurons [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…However, alterations in the breathing-related modulation of hypoglossal motoneurons have been considered to be involved in sleep obstructive apnea [28][29][30]. Previous studies have shown that during specific experimental conditions, such as hypercapnia-hypoxia or lung inflation, the XII rhythmic activity might not be perfectly coupled to other respiratory motor outputs such as phrenic motoneurons [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…This explains sudden death from snake bites [321,322], vaccines [323][324][325][326][327][328][329][330][331][332][333], and cocaine [215], in otherwise healthy people, as examples. Depending on their surfactant property and their position within the Hofmeister series, environmental biological or chemical intoxicants of virtually any type can provide the EIWS to induce SDS.…”
Section: Discussionmentioning
confidence: 99%
“…The arcuate nucleus is an important cardiorespiratory center in the medulla and hypoplasia of this nucleus has been detected in over 50% of infants dying of SIDS (105). Alterations in another brainstem nucleus have also been demonstrated (85, 107112). Some of these nuclei (e.g., nucleus ambiguus, parabrachial nucleus) also participate in the reflex arc of TCR (40, 42).…”
Section: Role Of Tcr In Sudden Infant Death Syndromementioning
confidence: 94%